(untitled) (African Journal of Biomedical Research, 2022)
Human immuno deficiency virus (HIV) infection is a pandemic disease, and many cellular and systemic factors are known to be affected and altered. Anemia has been shown to be a common complication of HIV infection. The study aimed to assess the impact of HIV infection on hepcidin and iron indices since hepcidin is an iron regulatory protein. A total of ninety subjects were investigated which consisted of fifty subjects living with HIV and forty apparently healthy subjects served as control. Twenty nine of the HIV subjects were on antiretroviral therapy (ART); emtricitabine, zidovudine, tenofovir and lamivudine in different combinations. Hepcidin was estimated using a solid phase enzyme-linked immunosorbent assay (ELISA) which is based on the principle of competitive binding. Serum iron, unsaturated iron binding capacity (UIBC) and total iron binding capacity (TIBC) were estimated using the spectrophotometric method. The result showed significant increase (p<0.05) in unsaturated iron binding capacity (UIBC) of HIV subjects compared with control. Although, there was no significant negative impact of HIV infection on hepcidin and the iron indices, the study concluded that the parameters should be measured to monitoring the progress of HIV infection in order to prevent anemia which may occur during HIV infection.